Policing the 'Anti-Social' Tourist. Mass Tourism and 'Disorderly Behaviors' in Venice, Amsterdam and Barcelona. - Alexander Araya López (Coordinamento SIBA, 2020)
In the last years, several cities in Europe and around the world have witnessed the emergence of social movements critical of mass tourism, underlining a diversity of 'externalities' associated to this highly-complex global industry. The so-defined 'anti-social' (i.e. unruly, offensive, inappropriate) behavior of tourists has been highlighted by both social movements and the local and global media among these negative effects of tourism, and local authorities have responded with many campaigns and strategies to regulate the impact of visitors in the lives of locals. By focusing on three European city-cases (namely Amsterdam, Venice and Barcelona), this paper discusses the current efforts to regulate 'disruptive behavior', while examining the limits of these initiatives and the challenges that these approaches create to the daily management of public spaces.